Evaluating the energy regulatory hormones of nesfatin-1, irisin, adropin and preptin in multiple sclerosis - Algul, Sermin; Ozcelik, Oguz (Elsevier BV, 2022)
Nesfatin-1, irisin, adropin and preptin were originally introduced as energy regulatory hormones. However, the results of studies revealed that these hormones may also have important roles in inflammation, immune function and neurological impairment. Multiple sclerosis (MS) is a chronic autoimmune disease, characterized by progressive inflammation, demyelination, and axonal loss in the central nervous system. We aimed to evaluate nesfatin-1, irisin, adropin and preptin hormones in patients with MS accompanied by inflammation and central nervous system dysfunction.A total of 110 subjects (65 patients with relapsing-remitting MS and 45 healthy individuals as control group) were included in this study. Venous blood samples were collected between 7:30 a.m. and 9:00 a.m. Serum concentrations of all markers were measured by enzyme linked immunoassay methods. The unpaired t-test was used to investigate between-group differences.The nesfatin-1, irisin, adropin and preptin levels were found to be significantly lower in the MS group compared to the control group (p < 0.05).In the present study, circulating nesfatin-1, irisin, adropin and preptin levels were decreased in patients with MS. However, the pathogenesis of MS and the underlying molecular mechanism of these hormones in MS have still not been elucidated. Further investigations with larger sample sizes and longer periods are required to obtain satisfactory information. In conclusion, the energy regulatory hormones of nesfatin-1, irisin, adropin and preptin may have potential for the development of new therapeutic targets for treatment of inflammatory diseases.
Keywords: Multiple Sclerosis; Humans; Intercellular Signaling Peptides and Proteins; Blood Proteins; Peptides; Hormones; Fibronectins; 3. Good health